A Study on the Linkage between Age and Education Levels in Adaption of Artificial Intelligence by Banking Customers in Bengaluru - Dr. Chaya. R; Syed Salman (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2023)
In many areas of our lives, including banking services, artificial intelligence (AI) has been rapidly integrated. The present study will explore the factors that influence the adoption of artificial intelligence (AI) by banking customers. Specifically, it will investigate the relationship between age and education and their impact on the acceptance and use of AI in the banking industry. With the help of a literature review and primary data analyses, the Pearson correlation coefficient is used to measure a correlation that measures the strength and direction of the relationship between variables. Further the hypothesis are tested based on the Pearson correlation coefficient analysis.